A comparison of quality of life between patients with small and large gastric remnant volumes after gastrectomy for gastric cancer. Issue 33 (20th August 2021) - Min, Jae-Seok; Jeong, Sang-Ho; Park, Ji-Ho; Kim, Taehan; Jung, Eun-Jung; Ju, Young-Tae; Jeong, Chi-Young; Kim, Ju-Yeon; Park, Miyeong; Lee, Young-Joon
Abstract : Abstract: The impact of gastric remnant volumes (GRVs) after gastrectomy on patients' quality of life (QOL) has not yet been clarified. The aim of the present study was to compare QOL after gastrectomy between small and large gastric remnant volume patients. We prospectively collected clinical data from 78 consecutive patients who underwent distal gastrectomy with Billroth II gastrojejunostomy for gastric cancer. The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Stomach questionnaire and gastric computed tomography scans were performed. The patients were subdivided into 2 groups by remnant stomach volume (the S group ⩽110 mL vs L group >110 mL). The worst scores for most items were observed at postoperative month 1 and usually improved thereafter. There was no difference in the STO22 score except for dysphagia between the S and L groups after gastrectomy ( P  > .05). The QOL score of dysphagia was different at postoperative 6 months (S vs L, 12.4 vs 22.8, P  < .03), but there was no difference at postoperative months 1, 3, 12, 24, or 36 ( P  > .05). The remnant gastric volume after partial gastrectomy affects neither functional differences nor QOL after 6 months following appropriate radical surgery.